Emergence of a butterfly: the life experiences of type 1 diabetes Taiwanese patients during the 16–25 years old transition period. Issue 1 (1st January 2020) - Chiang, Yueh-Tao; Yu, Hsing-Yi; Lo, Fu-Sung; Chen, Chi-Wen; Huang, Tzu-Ting; Chang, Chi-Wen; Moons, Philip
ABSTRACT: Purpose : To explore the life experiences of patients with type 1 diabetes transition from adolescence into adulthood in Taiwan. Methods : Descriptive phenomenological design was used. Fourteen participants were individually interviewed using a semi-structured interview. Results : The life experiences of patients with type 1 diabetes transition from adolescence into adulthood experience a metamorphosis from awareness of responsibility to figuring out a way to care for themselves. Six themes emerged: (1) hibernation: awareness of responsibility; (2) emergence: attempts to take responsibility; (3) perseverance: encountering difficulties; (4) anxiety: multiple worries; (5) hesitation: back-and-forth, " and (6) exit: finding a way out." Conclusions : During the transition phase, the participants experienced the trials of various situations. Regardless of whether they are able to independently bear the responsibilities of self-management, they all hope to turn around the challenges of disease control and take ownership of their disease. Like a butterfly that emerges from a cocoon, they hoped to overcome the dangers of taking flight through trial and error and navigating the world. The results of this study can serve as a reference for clinical care and developing localized intervention strategies targeted to the transition period between adolescence and young adulthood.